Impact of Bioenergy on Economic Growth and Development: An European Perspective - Stavros Kalogiannidis; Fotios Chatzitheodoridis; Stamatis Kontsas; Dimitrios Syndoukas (International Journal of Energy Economics and Policy, 2023)
The development of a country's economy depends heavily on its access to energy. It is extensively used in agriculture and related industries, including the production and delivery of fertilisers, pesticides, and farm equipment. This study investigated the impact of Bioenergy on economic growth and development in Europe with major focus on Greece. The study used a questionnaire to collect data from 400 professionals in the energy sector in Greece. The study showed that increased bioenergy production positively affects economic growth and development. It was established that there is a significant relationship between dependence on renewable and low-carbon energy systems and investing in sources of bioenergy positively affect economic growth and development. Households require bioenergy for heating, lighting, and cooking. Electricity, coal, petroleum, natural gas, uranium, and other fuels can all be used to produce energy. Bioenergy influences a state's economic performance and a good correlation with the level of innovation in the industry or with energy derived from natural gas. The article discusses the disparity in bioenergy use across nations as well as how they have changed during the investigated time. All of these factors lend credence to the advantages that bioenergy will bring about for the long-term growth of the bioeconomy. Production of bioenergy has the potential to significantly reduce climate change while long-term energy resource diversification is guaranteed.